MUTU SABUN MANGKOKAN (Nothopanax scutellaium Merr) - G. R. Hanum; S. Ardiansyah (FMIPA : Universitas PGRI Adi Buana, 2018)
Mangkokan soap (Nothopanax Scutellaium Merr) is made from extract of mangkokan leaf and the material making of soap there are oil, NaOH, alcohol and glycerin. This research is to find out the quality of microbiology and chemical soap of mangkokan leaf extract (Nothopanax Scutellaium Merr) with 90% concentration of mangkokan leaf extract . This research is an experimental research with descriptive of data analysis. The results of this study were microbiological quality of Mangkokan extract soap(Nothopanax Scutellaium Merr) has antibacterial activity to Escherichia coli bacteria and there is no microbial contamination. Chemical quality of Mangkokan Extract Soap (Nothopanax Scutellaium Merr) was tested on free alkali level test 0%, pH value 11,03 and water content value 0,4668%. Keywords: Escherichia coli, Mangkokan Leaf, Soap.